The Improvement Of Mathematics Learning Outcomes With Think Pair Share Cooperative Learning Model - Rondang Harianja; Carolina Lita Permatasari (JME (Journal of Mathematics Education), 2022)
In the process of mathematics learning, many students are less active, many are noisy, the work given is not completed, and the results of student evaluations are not satisfactory. For this reason, appropriate learning improvements are needed, namely by applying the think pair share cooperative learning model. This study aims to improve mathematics learning outcomes through think pair share cooperative learning method (think, pair, share) for Marsudirini Perawang  elementary school students. The research subjects were students of grade 3 (three) totaling 30 people. The type of research is classroom action research. The research procedure consisted of planning, implementing actions, observing, and reflecting. The research instruments are learning tools and data collection tools (test sheets and student observation sheets).  The results showed that the students' scores had increased very well from 0% then 10% to 26%. In the daily test score of 1, the number of students who achieved the very good category increased by 10%. Meanwhile, in the daily test score of 2, the number of students who achieved the very good category increased to 26%. The average score of students on the second daily test increased above the minimum completeness criteria (KKM) that had been determined by the school (7370). Student activities in the aspects of answering questions, discussing student worksheets and reporting discussion results have increased. In the first cycle the average was 17.3% and 35.3%. While in the second cycle it rose to 53% and 73.3%. Overall, the average student activity in the first cycle was 18.12% and in the second cycle 63.33%. Thus, the application of think pair share cooperative learning model can improve mathematics learning outcomes in grade 3 (three) elementary school students.